2013
DOI: 10.1128/aem.03527-12
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Treatment Effluent Reduces the Abundance and Diversity of Benthic Bacterial Communities in Urban and Suburban Rivers

Abstract: bIn highly urbanized areas, wastewater treatment plant (WWTP) effluent can represent a significant component of freshwater ecosystems. As it is impossible for the composition of WWTP effluent to match the composition of the receiving system, the potential exists for effluent to significantly impact the chemical and biological characteristics of the receiving ecosystem. We assessed the impacts of WWTP effluent on the size, activity, and composition of benthic microbial communities by comparing two distinct fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
162
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(199 citation statements)
references
References 49 publications
(48 reference statements)
22
162
3
Order By: Relevance
“…A similar observation of increase in electrical conductivity downstream as a result of industrial and anthropogenic activities on freshwater systems has been documented (Liu et al, 2012;Drury et al, 2013;Jordaan and Bezuidenhout, 2016). Sulphate level was consistent in upstream and downstream at location 1 but a slight increase of sulphate concentration downstream of location 2 was observed.…”
Section: Resultssupporting
confidence: 57%
“…A similar observation of increase in electrical conductivity downstream as a result of industrial and anthropogenic activities on freshwater systems has been documented (Liu et al, 2012;Drury et al, 2013;Jordaan and Bezuidenhout, 2016). Sulphate level was consistent in upstream and downstream at location 1 but a slight increase of sulphate concentration downstream of location 2 was observed.…”
Section: Resultssupporting
confidence: 57%
“…However, their abundance may be a feeble indicator of pathogens in environmental waters. Efficient treatment processes, coupled with tertiary treatment steps such as disinfection, can reduce the pathogen loads and other physicochemical contaminants such as biochemical oxygen-demanding substances and nutrient contents, in order to protect human health and the freshwater ecosystems from pollution [20]. E. coli, Shigella, Salmonella and Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that reclaimed water contains residue of halogenated hydrocarbons, heavy metal, antibiotics and other drugs contaminate groundwater when it replenishes river channels, which may produce detrimental effects on microbial communities (Drury et al, 2013). In the case of those pollutants, substantial changes happened in bacterial structure and composition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in contrast to the upstream, the richness, evenness and diversity of bacterial community in the pool below was extremely low, indicating that there may have been a secondary effect from the RWTP effluent affecting the bacterial community characteristic near the outfall. It is well known that RWTPs are a significant source of disinfection byproducts, antibiotics, heavy metals, pharmaceuticals and pesticides, which may produce detrimental effects on microbial communities (Drury et al, 2013;Proia et al, 2013). Based on these observations, we expected that microbial diversity may be affected by some toxic compounds containing RWTP effluent, which might have contributed to a decrease in bacterial diversity from near the outfall sites, while the recovery of wetland ecosystem by the wetland plant rhizosphere microorganism associated with plants contributed to the rise in bacterial diversity and species richness at the downstream location (Stottmeister et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation